2008
DOI: 10.3168/jds.2008-1029
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Evaluation of Fertility Traits of Dairy Cattle Using a Multiple-Trait Animal Model

Abstract: A genetic evaluation system was developed for 5 fertility traits of dairy cattle: interval from first to successful insemination and nonreturn rate to 56 d of heifers, and interval from calving to first insemination, nonreturn rate to 56 d, and interval first to successful insemination of cows. Using the 2 interval traits of cows as components, breeding values for days open were derived. A multiple-trait animal model was applied to evaluate these fertility traits. Fertility traits of later lactations of cows w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

28
69
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(102 citation statements)
references
References 8 publications
28
69
4
Order By: Relevance
“…Weigel and Rekaya, 2000;Ranberg et al, 2003). Genetic correlations among various fertility traits generally agreed with previous findings (Kadarmideen et al, 2003;Liu et al, 2008). Consistent with our results, Kadarmideen et al (2003) reported genetic correlations among fertility traits were generally high.…”
Section: Genetic and Phenotypic Correlationssupporting
confidence: 92%
“…Weigel and Rekaya, 2000;Ranberg et al, 2003). Genetic correlations among various fertility traits generally agreed with previous findings (Kadarmideen et al, 2003;Liu et al, 2008). Consistent with our results, Kadarmideen et al (2003) reported genetic correlations among fertility traits were generally high.…”
Section: Genetic and Phenotypic Correlationssupporting
confidence: 92%
“…Jamrozik et al (2005), Tsuruta et al (2009) and Bastin et al (2010) estimated that the heritabilities of NR to 56 days at first lactation in Canadian Holstein cows were 0.020 and 0.026, respectively. Liu et al (2008) also reported that the heritabilities of NR to 56 days, as estimated from 25.5 million insemination records, were 0.012 for heifers and 0.015 for dairy cows in Germany, Austria and Luxembourg. Our heritability estimates for CR were in the range of those recently reported for CR or NR for dairy cows.…”
Section: Discussionmentioning
confidence: 98%
“…Many indicators of female fertility are used, including days open (DO), calving interval (CI), days from calving to first service (DFS), non-return rate (NR) and CR at first service (Liu et al, 2008). Interval traits (DO, CI and DFS) are used only for cows, because those traits are estimated by using information associated with calving.…”
Section: Introductionmentioning
confidence: 99%
“…For these reasons, the selection programs are often confronted with the challenge of maintaining satisfactory reproductive performances and high levels of milk production (Weigel and Rekaya, 2000). Therefore, it is necessary to include fertility traits in the selection programs in order to improve fertility or minimize the deterioration of these traits (Liu et al, 2008;Ghiasi et al, 2011). Heritability estimates of reproductive performance were low and ranged from zero to 0.1 (Muir et al, 2004;Sewalem et al, 2010;Ghiasi et al, 2011).…”
Section: Introductionmentioning
confidence: 99%